Living in the margins, filling in the gaps: the making of the Coloured Community of Durban. A social and political history - Nichol, Vanessa (My University, 2021)
The thesis examines the formation and evolution of a community borne of the offspring of settlers, locals, and immigrants from Mauritius, St. Helena and the Cape, who settled in the city of Durban. These disparate groups were drawn to each other by their 'sameness', as well as by their 'otherness' and pushed together by the state into a group named Coloured. The thesis charts institutions and spaces developed for the community by the authorities and those that were started by the group itself and follows the Coloured lives lived therein. Through life history interviews with community elders, and a weaving together of data from archives, newspapers and the literature, the thesis provides the first comprehensive piece of research on the history of Coloured community of Durban. The history shows that this Coloured community carved out a creolised place in the city on the margins of white, Indian and African life and culture. The small size of the group meant that it was less of a threat to any of the other major groups vying for dominance and was largely left alone; at the same time, a closeness in language and religion allowed the group access to Colonial and city authorities to gain various privileges. Apartheid ended special considerations, and the community reluctantly joined national movements for better conditions and equal rights. This history of Coloured people in Durban shows the evolution of a fluid, pragmatic and introspective group; reacting to outside forces through acts of survival and creating community and identity from within
A thesis submitted to the Faculty of Humanities, in fulfilment of the requirements for the degree Doctor of Philosophy in History, University of the Witwatersrand, 2021